BIMBINGAN TEKNIS TAMPILAN JADWAL SHOLAT DI MUSHOLLA AL-KHOIR DESA TEGAL WERU KABUPATEN MALANG - Leonardo Kamajaya; Fitri Fitri; Lucky Nindya Palupi; Eka Mandayatma; Sidik Nurcahyo; Agus Sukoco Heru Sumarno; Fauziah Sholikhatun Nisa (Publisher UPT P2M Politeknik Negeri Malang, 2022)
This activity aims to design an information system that contains prayer time schedules and other important information that is very useful for musholla Al-Khoir pilgrims. The purpose of the activity is to provide technical guidance to the mosque administrators. The result of this activity is that people in the Tegal Weru area become easier to find out the prayer schedule and other important information related to worship activities